Multimedia computer-assisted instruction for carers on exercise for older people: Development and testing - Muthita Ponpaipan (2018)
Aim. This paper is a report of a study conducted to develop a multimedia computer-assisted instruction for informal carers and test its content validity, user difficulty and user satisfaction.Background. Healthy ageing is an increasingly important public health target globally. Changes in technology offer the opportunity for e-health promotion as a means of educating populations and healthcare staff to meet public health targets.Methods. Computer-assisted instruction was developed and tested systematically in four phases during 2008, and these are outlined. Phase 1 consisted of topic and content identification using a literature review. Phase 2 comprised refinement of the content using an academic panel of experts. Phase 3 was the production of computer-assisted instruction comprising problem clarification, algorithm designing with reference to a cognitive theory of multimedia learning and program coding. Phase 4 consisted of testing for content validity, and writing a computer-assisted instruction manual and testing it for user difficulty and satisfaction.Results. The data from each phase informed the development and refinement of the computer-assisted instruction. Content validity was confirmed and 'test' users reported few difficulties in its use and high satisfaction.Conclusion. This e-health promotion initiative is an example of how computer-assisted instruction may be developed to teach carers of older people. © 2010 Blackwell Publishing Ltd.